Respuesta :
Answer:
x=-3
Step-by-step explanation:
-6x-3(1+5x)=-8(x-4)+4
Step 1. Distribute:
-6x-3-15x=-8x+32+4
Step 2. Combine like terms:
-21x-3=-8x+36
Step 3. Add to different sides:
-13x=39
Step 4. Solve for x:
x=-3
-
Answer:
[tex]x=-3[/tex]
Step-by-step explanation:
Given Equation:
[tex]-6x-3(1+5x)=-8(x-4)+4[/tex]
[tex]-6x-3(1)-3(5x)=-8(x)-8(-4)+4\\\\-6x-3-15x=-8x+32+4\\\\-6x-15x-3=-8x+36\\\\-21x-3=-8x+36\\\\[/tex]
Adding '[tex]8x[/tex]' both the sides:
[tex]-21x+8x-3=-8x+8x+36\\\\-13x-3=36[/tex]
Adding '3' both the side:
[tex]-13x-3+3=36+3\\\\-13x=39\\\\x=\frac{39}{-13} \\\\[/tex]
[tex]x=-3[/tex]